Sistem Profiling Lulusan Fakultas Teknologi Informasi Universitas Atma Jaya Makassar - Kustanto, Fransisca (TEMATIKA, Journal of Informatics and Information Systems, 2017)
Information technology faculty has a tracer study do once of 4 year and using the method telephone survey, has several constraints are the cost prohibitive and graduates difficult to remember the study materials and the courses are used. The graduates have the research now only recording title the research, include the research in hard copy, but has some deficiency are limited storage, difficulty finding and finding the research and if the research and cd is lost or scattered, it is difficult to know and find the research and has no research group. We need the development from tracer study based on job description and alumni research, the information is needed to know success of the education process and to measure the performance of the study program through the resulting outputof graduates who can meet the demands of the era and reference for the development and implementation of the quality assurance system of education. In this research used waterfall method, produce an application capable of online registration and the process of entering personal and work data information is done by graduates voluntarily (self-interest) and research is submitted at the time of file collection, as well as evaluating performance and producing evaluation report of graduateÂ profile profile based on graduate work, research and overall (graduate work and final assignment).Keywords: Registration, Evaluation, Performance Graduate Profile, Tracer Study.